A Change in the Law Needs Serious Supporting Evidence - And It Isn't There. Issue 2 (1st January 2015) - Preston, Robert
<x content-type="archive" xml:space="preserve">Abstract</x> The central question in the assisted dying debate is whether the law should be changed to license doctors to supply lethal drugs to terminally ill people. No convincing evidence has been produced that the law that we have is not fit for purpose or that what would be put in its place would be better. Moreover, it is questionable whether the proposals being put forward meet the aims which are claimed for them. Nor do suggestions that there is currently no 'right to die' or that legislation is being blocked by the churches stand up to serious scrutiny.